A Common Fixed Point Theorem in Complex Valued Metric Spaces (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we have extended the contractive condition of Karapinar[5] and Noorwali[6] tocomplex valued metric space.2010 AMS Subject Classification: 47H10; 54H25